2020
DOI: 10.1111/ijac.13657
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure, and properties of polymer‐derived, metal‐reinforced boron carbide cermet composites

Abstract: We report on a novel polymer‐derived synthesis approach that yields boron carbide monoliths and metal‐reinforced B4C cermets. This single‐step approach relies on a preceramic powder blend of boron and an acetylenic resin with a high char yield. At low temperatures below 1500°C and without applied pressures, preceramic precursor reaction bond together and form nanocrystalline refractory B4C matrices. Resulting near net shape boron, carbide monoliths exhibit small crystal grain sizes, maintain chemical purity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…The medium‐intensity boron carbide diffraction peaks were the most intense and clear in the composite derivative with 20% B 4 C. Boron carbide density also suppressed the diffraction intensity at 21° caused by the PVA/PEO/PVP blend. Diffraction angles originating from boron carbide are clearly observed at approximately 23°, 25°, 35°, and 38° 29,30 . Figure 7B shows the XRD patterns of PVA 90 /PEO 5 /PVP 5 ‐BN %5 , PVA 90 /PEO 5 /PVP 5 ‐BN %10 , and PVA 90 /PEO 5 /PVP 5 ‐BN %20 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The medium‐intensity boron carbide diffraction peaks were the most intense and clear in the composite derivative with 20% B 4 C. Boron carbide density also suppressed the diffraction intensity at 21° caused by the PVA/PEO/PVP blend. Diffraction angles originating from boron carbide are clearly observed at approximately 23°, 25°, 35°, and 38° 29,30 . Figure 7B shows the XRD patterns of PVA 90 /PEO 5 /PVP 5 ‐BN %5 , PVA 90 /PEO 5 /PVP 5 ‐BN %10 , and PVA 90 /PEO 5 /PVP 5 ‐BN %20 .…”
Section: Resultsmentioning
confidence: 99%
“…28 According to the XRD pattern shown in Figure 6, it is confirmed that the interaction and miscibility between PVA, PVP, and PEO are due to the existence of the O H and C O groups and the strong interaction between them. 29,30 Figure 7B shows the XRD patterns of PVA 90 /PEO 5 /PVP 5 -BN %5 , PVA 90 /PEO 5 /PVP 5 -BN %10 , and PVA 90 /PEO 5 /PVP 5 -BN %20 . Boron nitrite, unlike boron carbide, shows less diffraction.…”
Section: Elemental Analysismentioning
confidence: 99%